1996
DOI: 10.1007/bf02437932
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer bias in human sexuality research: Evidence for both sexuality and personality differences in males

Abstract: The extent to which personality, social behavior, and sexuality differed in undergraduate males under two different types of recruitment, volunteer and nonvolunteer, was investigated. Nonvolunteers (N = 160) were ostensibly recruited for a study on personality, and volunteers (N = 204) were overtly recruited for a study on human sexuality. Both samples completed the same personality, social behavior, and sexuality questionnaires. Volunteers were found to be more sexually experienced, more interested in sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 31 publications
(46 reference statements)
3
53
1
Order By: Relevance
“…The fact that the participation rate was not uniform and differed among sociodemographic groups throughout the study period is rather disturbing, as the attitudes and sexual behavior of the non-responders may have differed from those of the responders. It has been shown in other studies that participants in national sexuality surveys had higher socioeconomic status, were better educated, were more sexually experienced, and had less conservative sexual attitudes than non-participants (Bogaert, 1996;Purdie, Dunne, Boyle, Cook, & Najman, 2002); however, this bias probably does not seriously compromise population estimates (Dunne et al, 1997). It has been asserted in previous investigtions that researchers generally overestimate participation effects in sex research and exaggerate the threat that questions on sexual behavior engender (Johnson & Delamater, 1976).…”
Section: Discussionmentioning
confidence: 93%
“…The fact that the participation rate was not uniform and differed among sociodemographic groups throughout the study period is rather disturbing, as the attitudes and sexual behavior of the non-responders may have differed from those of the responders. It has been shown in other studies that participants in national sexuality surveys had higher socioeconomic status, were better educated, were more sexually experienced, and had less conservative sexual attitudes than non-participants (Bogaert, 1996;Purdie, Dunne, Boyle, Cook, & Najman, 2002); however, this bias probably does not seriously compromise population estimates (Dunne et al, 1997). It has been asserted in previous investigtions that researchers generally overestimate participation effects in sex research and exaggerate the threat that questions on sexual behavior engender (Johnson & Delamater, 1976).…”
Section: Discussionmentioning
confidence: 93%
“…As much of the recruitment took place by distributing the AIS, participants were aware of the sexual nature of the study before participating. Previous studies have shown a volunteer bias in participation in sexualityrelated studies, with volunteers having more experience with sex (Bogaert, 1996;Strassberg & Lowe, 1995;Wiederman, 1999), and less traditional attitudes toward sex (Dunne et al, 1997;Wiederman, 1999) than non-volunteers. Consequently, it is possible that the control group had different attitudes toward sex than the general population, which may have exaggerated differences between groups.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…However, we acknowledge that even with these efforts, possible self-selection biases remain a concern and may impact the representativeness of the sample and the generalizability of the results. Previous research has shown that volunteers for sexuality-related studies tend to have a more positive attitude towards their own sexuality and more sexual experience than non-volunteers (e.g., see 46,47 ). However, studies have also found that volunteers for sex research are not distinguishable from non-volunteers on most general personality dimensions (e.g., 47 ).…”
mentioning
confidence: 99%